Da reprodução assistida às dificuldades de se tornar mãe de múltiplos bebês - Fonsêca, Célia Maria Souto Maior de Souza (2015)
Accounting for the responsibilities assigned to the new place reserved for the contemporary woman, who has often chosen to delay her motherhood project for later; when, finally, she decides to have children, her body no longer responds satisfactorily, forcing her, most of the time, to seek help by means of reproductive technologies. These, by the available resources and new procedures that add to the life span of women, have promoted a revolution in what is most ancient in human experience: the conception and motherhood. Face treatment, pregnancy and the giving birth to multiple babies have resulted in great challenges for the woman. This research is a qualitative study based on clinical psychology, in which the concepts of Winnicott s theory have been adopted. The condition of women seeking assisted reproduction which has resulted in them becoming mothers of multiple babies as well as trying to understand how to deal with such a condition has been researched. To accomplish this, three mothers of multiples were interviewed about their experience. Our study is justified by its importance and timeliness, including the benefits it can offer to the theme still in need of new theoretical contributions, especially about the psychological issues involved. For data analysis, the material was subdivided into categories and subcategories. By doing this the ambivalence experienced by these mothers before the paradox of an experience that exposes the contradiction between wanting to live and motherhood could be seen. For them, dealing with the "excesses" that this condition imposes the rigors of treatment, several attempts to get pregnant, miscarriages, and premature births - constitutes a "burden" too heavy to be supported, a permanent distress source and physical and emotional wear whose consequences still cannot be fully understood. The study also showed that there are other issues that eventually come to light from the conditions they faced when resorted to assisted reproduction. The experiment may have been exacerbated by the lack of care in various steps of the process. In addition, dealing with the problem of surplus embryos constituted an additional challenge, because it lacks specific legislation required for the discipline of this matter in our country. These issues, still little discussed in the literature, can stimulate the development of new studies.